2019
DOI: 10.5194/acp-2019-219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contributions of different sources to nitrous acid (HONO) at the SORPES station in eastern China: results from one-year continuous observation

Abstract: <p><strong>Abstract.</strong> Nitrous acid (HONO), a reservoir of the hydroxyl radical (OH), has been long-standing recognized to be of significant importance to atmospheric chemistry, but its sources are still debate. In this study, we conducted continuous measurement of HONO from November 2017 to November 2018 at SORPES station in Nanjing of eastern China. The yearly average mixing ratio of observed HONO was 0.69 ± 0.58&am… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 95 publications
3
4
1
Order By: Relevance
“…C HONO presented a strong correlation with ambient temperature (r ¼ 0.76) and a moderate relationship with RH (r ¼ 0.57), which was consistent with the study of Wen et al (2019) in a marine boundary layer. The average C HONO at our site was within the range of 0.43-3.36% h À 1 that determined from other studies around the world (Liu et al, 2019;Xu et al, 2015). Seasonal variation of C HONO has also been found by Liu et al (2019) at a suburban site in Nanjing in the subtropical zone with four distinct seasons.…”
Section: Nocturnal Hono Formationsupporting
confidence: 83%
See 2 more Smart Citations
“…C HONO presented a strong correlation with ambient temperature (r ¼ 0.76) and a moderate relationship with RH (r ¼ 0.57), which was consistent with the study of Wen et al (2019) in a marine boundary layer. The average C HONO at our site was within the range of 0.43-3.36% h À 1 that determined from other studies around the world (Liu et al, 2019;Xu et al, 2015). Seasonal variation of C HONO has also been found by Liu et al (2019) at a suburban site in Nanjing in the subtropical zone with four distinct seasons.…”
Section: Nocturnal Hono Formationsupporting
confidence: 83%
“…The average C HONO at our site was within the range of 0.43-3.36% h À 1 that determined from other studies around the world (Liu et al, 2019;Xu et al, 2015). Seasonal variation of C HONO has also been found by Liu et al (2019) at a suburban site in Nanjing in the subtropical zone with four distinct seasons.…”
Section: Nocturnal Hono Formationsupporting
confidence: 83%
See 1 more Smart Citation
“…However, the conversion ratio decreased when RH was over 80 %, like the HONO concentration. This phenomenon already reported, and Wojtal et al, suggested that it was caused by the surface loss or particle loss in marine boundary layers, which is in accordance with what we found in the present study discussed in section 3.1 (Liu et al, 2019b;Wojtal et al, 2011).Therefore, the observed HONO is likely to be formed through heterogeneous conversion which is mainly controlled by factors like NOx, RH, and surface area.…”
Section: Insight Into Hono Formation Mechanismsupporting
confidence: 93%
“…2A). Owing to the high HONO concentration accumulated throughout the night, the maximal POH-HONO in winter was as about 2-6 times of that was observed in the wintertime of Colorado, USA (~0.59 ppb h -1 ) (Kim et al, 2014), New York, USA (~0.40 ppb h -1 ) (Kanaya et al, 2007) and Nanjing, China (0.900.27 ppb h -1 ) (Liu et al, 2019b). In the period from April to June, the daily maxima of POH-HONO and POH-O3 were 2.481.42 × 10 7 molecules cm -3 s -1 (3.481.99 ppb h -1 ) and 6.514.17 × 10 7 molecules cm -3 s -1 (9.155.86 ppb h -1 ), respectively.…”
Section: Promotion Effect Of Hono Photolysis On Aerosol Formation In mentioning
confidence: 93%